Peran penyuluhan oleh Bhabinkamtibmas dalam pencegahan tindak pidana anak sebagai korban di wilayah hukum Polres Sumedang - Fahacer, Muhammad Mardani (Advances in Police Science Research Journal, 2020)
Crimes against children as victims in the Sumedang region have a high number. This should not have happened because children are the next generation of the nation that should be protected. Sumedang Regional Police as a state apparatus that becomes a law enforcer, protector, patron, and public servant in handling criminal cases against children as victims is considered to be less than optimal. This can be seen from the increase that occurred in the last 2 years which was dominated by sexual violence. The purpose of this study is to describe the role of counseling by the Sumedang District Police Bhabinkamtibmas as implementing subjects in preventing the crime of child victims and discovering the factors that cause the crime of child victims in the Sumedang Region. In this research, the implementation of the Bhabinkamtibmas task to prevent the crime of child victims uses role theory, management, theories, communication theory, and by paying attention to their suitability with the Community Policing concept, binluh concept, and the child concept. This research was conducted with a qualitative approach and type of field research. With data collection techniques of observation, interviews, and study documents. Data analysis techniques used include data reduction, data presentation and drawing conclusions. The results of the study and conclusions of this study indicate that based on data obtained and interviews with the Chief of Police, Kasat Binmas, Head of PPA, Bhabinkamtibmas, and the Office for the Protection of Women and Children in Sumedang stated that participation in efforts to prevent the crime of victims of children has not been thoroughly carried out using elements management and role elements. The factors that cause the crime of child victims are internal and external factors. Internal factors consist of quality personnel, and implementation planning. While external factors include coordination, cooperation, and legal awareness.